Comparative study on the digestion and absorption characteristics of n-3 LCPUFA-enriched phospholipids in the form of liposomes and emulsions. (November 2020) - Jiang, Shan; Zhang, Tian-Tian; Cong, Pei-Xu; Xu, Jie; Xue, Chang-Hu; Jiang, Xiao-Ming; Wang, Yu-Ming
Graphical abstract: Highlights: DHA/EPA-PC liposome had higher peak value in serum DHA/EPA levels than emulsion. DHA/EPA-PC liposome got a peak in serum DHA/EPA levels at 3 h after administration. DHA/EPA-PC liposome showed high levels of total PL in serum for a substantial period. DHA/EPA-PC liposome was hydrolyzed slower by PLA2 than emulsion in small intestine. Abstract: Previous studies have reported that phospholipids rich in n-3 long-chain polyunsaturated fatty acids (n-3 LCPUFA) in the form of liposome exhibited superior bioactivities than other formulation. However, the digestion and absorption characteristics of n-3 LCPUFA-enriched phospholipids were still unclear, restricting the molecular mechanism analysis related to their distinctive activities. The aim of the present study was to compare the digestion and absorption characteristics of DHA/EPA-PC in the forms of liposome and emulsion. The fatty acid composition and lipid species in serum, intestinal wall and content of healthy mice were determined after oral administration with DHA/EPA-PC. Results showed that the peak value of serum DHA/EPA level in the liposome group was significantly higher than that of the emulsion group ( p < 0.05), although the peak in the liposome group appeared at 3 h and the peak time was 2 h in the emulsion group. Lipidomics analysis indicated that the high levels of total PL and PL-DHA could be retained in serum for a substantial period after administration of the DHA/EPA-PC liposome, which might be attributed to that the DHA/EPA-PC in the form of liposomes was hydrolyzed slower by pancreatic phospholipase A2 than the emulsion form in small intestinal content. The obtained results might provide theoretical basis for the development and utilization of marine-derived phospholipids.